A Comparative Performance Analysis of Modified Dӧmӧsi’s Cryptosystem and Data Encryption Standard - Khaleel, G; TURAEV, SHERZOD; Tamrin, M I M; Al-Shaikhli, Imad F (International Journal on Perceptive and Cognitive Computing, 2017)
The performance has a central importance for all cryptosystems. This paper aims to provide a framework and platform to evaluate a performance of Modified Dӧmӧsi’s Cryptosystem, a stream cipher based on finite automata, comparing to Data Encryption Standard. The performance is evaluated in terms of encrypting time and throughput.